2006
DOI: 10.1097/01.pcc.0000192319.55850.81
|View full text |Cite
|
Sign up to set email alerts
|

Variation in pediatric intensive care therapies and outcomes by race, gender, and insurance status*

Abstract: Risk-adjusted mortality and resource use for critically ill children did not differ according to race, gender, or insurance status. Policies to expand health insurance to children appear more likely to affect physiologic derangement on admission rather than technical quality of care in the pediatric intensive care unit setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 38 publications
(37 reference statements)
5
54
1
Order By: Relevance
“…The most severe incidents were respiratory in nature, which might be due to the fact that accidental extubations were included in this group and were all considered of major severity. We had 0.74 unplanned extubations per 100 ventilator days, less than other authors have described [13,14,22] and similar to rates reported by Ligi and co-workers [12]; however, the case mix should be considered when comparing rates of accidental extubations. Similar to the study of Veldman et al [26], only two of the ten patients had to be re-intubated.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The most severe incidents were respiratory in nature, which might be due to the fact that accidental extubations were included in this group and were all considered of major severity. We had 0.74 unplanned extubations per 100 ventilator days, less than other authors have described [13,14,22] and similar to rates reported by Ligi and co-workers [12]; however, the case mix should be considered when comparing rates of accidental extubations. Similar to the study of Veldman et al [26], only two of the ten patients had to be re-intubated.…”
Section: Discussionsupporting
confidence: 79%
“…Other authors found a higher mortality rate of boys in Table 3 Logistic regression analysis of probable explanatory factors for whether a patient is affected by critical incident(s) or not a non-premature paediatric cardiac ICU population treated with ECMO [14]. On the contrary, Lopez et al did not find differences in standardized mortality ratio related to gender in their multicenter PICU study [13]. It is not clear whether the longer length of stay we found in the CI group is caused by CIs or whether the risk to experience a CI is higher due to the patients' longer stay in circumstances where invasive procedures, bustle and a high turnover of patients are very common [12].…”
Section: Discussionmentioning
confidence: 91%
“…Also, this finding is in agreement with the study of Lopez [1] who stateed that the majority of patients admitted in the PICU for five years were males (57.5%). At the end of their study, they demonstrate that there is no difference between both genders regarding outcomes.…”
Section: Results:-supporting
confidence: 82%
“…Iantorno et al [8] reported no sex-or race-based treatment disparities in the use of pulmonary artery catheterization in the adult ICU population, and Erickson et al [50] did not find any disparities in hospital mortality or ICU length of stay in adult ICU patients. In the pediatric population, both Lopez et al [9] and Epstein et al [9,10] found no difference in pediatric ICU mortality based on race/ethnicity but did find that severity of illness at the time of ICU admission was higher for the uninsured and government-insured patients. Although convincing evidence for disparities in ICU health care based on race/ethnicity is lacking, most inequities in health care in the ICU seem to be based on socioeconomic status and health insurance [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 95%